Adaptation assessment and analysis of economic growth since the market reform in China - Chongqiang Ren; Guofang Zhai; Shutian Zhou; Shasha Li; Wei Chen (Kiel Institute for the World Economy (IfW), 2017)
China has experienced extraordinary institutional and socio-economic changes after 1978, and its deepening reform to market-oriented economy since 1990s was also recognized as one the most significant factors to drive China's rise in the contemporary world. Although many aspects of China's market reform have been extensively analysed in the literature, specific attention on the adaptation of economic growth to this reform has been relatively ignored. To fill this gap, this research adopts the extenics assessment method to assess this adaptation and applies the membership function coordination degree model to analyse the sustainability of such adaptation. In conclusion, China has demonstrated a significantly enhanced adaptation capacity at the expense of coordination, which requires to be further emphasised in its economic growth adaptation strategies.
Keywords: A11; O11; P21; P41; 330; economic adaptation; extenics assessment method; membership function coordination degree model; market economy reform